2023
DOI: 10.1111/cns.14120
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein decoy peptide protects mice against α‐synuclein‐induced memory loss

Abstract: Aims We previously found that a decoy peptide derived from the C‐terminal sequence of α‐Synuclein (αSyn) prevents cytotoxic αSyn aggregation caused by fatty acid‐binding protein 3 (FABP3) in vitro. In this study, we continued to utilize αSyn‐derived peptides to further validate their effects on αSyn neurotoxicity and behavioral impairments in αSyn preformed fibrils (PFFs)‐injected mouse model of Parkinson's disease (PD). Methods Mice were injected with αSyn PFFs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…It was found that FABP3 can bind to α-synuclein in a 1:1 ratio, promoting α-synuclein-FABP3 aggregate formation [115]. Consequently, we attempted to create a drug that could inhibit the interaction between FABP3 and α-synuclein [126,142].…”
Section: Therapeutic Potential Of Fabp-targeting Drugs For Parkinson'...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that FABP3 can bind to α-synuclein in a 1:1 ratio, promoting α-synuclein-FABP3 aggregate formation [115]. Consequently, we attempted to create a drug that could inhibit the interaction between FABP3 and α-synuclein [126,142].…”
Section: Therapeutic Potential Of Fabp-targeting Drugs For Parkinson'...mentioning
confidence: 99%
“…The FABP3 ligand effectively prevents the degeneration of dopaminergic neurons and restores motor dysfunction to a healthy level in a Parkinson's disease mouse model [126]. Additionally, an α-synuclein mimicking peptide that inhibits the binding and aggregate formation of α-synuclein-FABP3 is capable of restoring memory and learning abilities in a Parkinson's disease dementia mouse model [142]. This peptide has the potential to alleviate α-synuclein phosphorylation, which links to neurotoxicity.…”
Section: Therapeutic Potential Of Fabp-targeting Drugs For Parkinson'...mentioning
confidence: 99%
“…Notably, FABP3 colocalizes with α-synuclein aggregates and contributes to mitochondrial dysfunction and the loss of tyrosine hydroxylase, a rate-limiting enzyme in dopamine synthesis [4,9]. Encouragingly, the inhibition of FABP3 using small-molecule ligands and peptides has demonstrated the ability to prevent FABP3-induced neurotoxicity [6,[10][11][12]. These findings highlight FABP3 as a potential target for addressing α-synuclein pathology and its associated effects.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides are well suited to be evaluated as potential aggregation inhibitors and/or potential α-synuclein disaggregators, thus reversing the ongoing neurodegeneration [15]. Most of the peptides proposed are fragments/or mutated fragments of the NAC (nonamyloid-β-component) domain as well as of the N-terminus of the α-synuclein or pre-NAC domain [16][17][18], the NAC-region and C-terminal region from a peptide library spanning the entire α-synuclein sequence [19], a larger library [20,21] and purified from natural sources, such as the peptide YIAEDAER from the marine snail Neptunea arthritica cumingii [22]. Established by segmenting all proteins deposited in the Protein Data Bank, the database proposed in [23] is centered on sequences adopting β-structures, specifically those identical or very similar to the regions of α-synuclein that are involved in aggregation.…”
Section: Introductionmentioning
confidence: 99%